2021
DOI: 10.21037/atm-21-176
|View full text |Cite
|
Sign up to set email alerts
|

Kindlin-2 regulates the differentiation of 3T3-L1 preadipocytes: implications for wound healing

Abstract: Background: Adipose tissue has been proven to play a crucial role in wound healing, while kindlin-2, an integrin-associated protein, has been shown to regulate cell adhesion, migration, and differentiation. This study aimed to explore its involvement in the cell differentiation of 3T3-L1 preadipocytes and its role in wound healing.Methods: Cell adhesion, Cell Counting Kit-8 (CCK-8), Transwell, and in vitro wound healing assays, along with adipogenic and osteogenic differentiation induction were performed in 3T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Studies have shown that preadipocytes, which are highly migratory fibroblast-like stem cells, facilitate wound healing. [ 10 ] Previous studies on transgenic mice have shown this effect can be explained by the role of adiponectin, which is a potent mediator of wound healing through re-epithelialization and angiogenesis. [ 11 ] In addition, adiponectin promotes preadipocyte proliferation and migration, serving as a potential therapeutic approach to treating surgical wounds in complex cases such as this patient.…”
Section: Clinical Discussionmentioning
confidence: 99%
“…Studies have shown that preadipocytes, which are highly migratory fibroblast-like stem cells, facilitate wound healing. [ 10 ] Previous studies on transgenic mice have shown this effect can be explained by the role of adiponectin, which is a potent mediator of wound healing through re-epithelialization and angiogenesis. [ 11 ] In addition, adiponectin promotes preadipocyte proliferation and migration, serving as a potential therapeutic approach to treating surgical wounds in complex cases such as this patient.…”
Section: Clinical Discussionmentioning
confidence: 99%
“…Skin tissue and cellular protein extraction and Western blotting were performed according to our previous protocols [ 45 ]. All the antibodies are presented in Supplementary Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry performed on paraffin sections and immunofluorescence staining performed on cells were described in our previous study [ 45 ]. For tissue immunofluorescence staining, sections were permeabilized using 0.2% Triton X-100 before blocking using 20% goat serum and then incubated with primary antibodies at 4 °C overnight.…”
Section: Methodsmentioning
confidence: 99%